Hukum Itu Beredar Pada ‘Illatnya - A, Asrullah; Musyahid, Achmad; Akmal, Andi Muhammad (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2025)
The concept of ‘illat in the proposal of fikih as the basis of the establishment and change of Islamic law. By raising the principle of “al-ḥukmu yadūru ma‘a ‘illatihi wujūdan wa ‘adaman” (the law revolves along with its ‘illat, existence or non-existence), the author explains that social change and cultural context can affect the applicability of Islamic law. ‘Illat is defined as a real property that is the rational basis of a Sharia law’. This article studies the various definitions of ‘illat according to the scholars usul fikih and describe the kinds of ‘illat based on the permanence of the Shari’ah’ and considerations of goodwill. Thus, an understanding of ‘illat becomes essential in order to ensure that Islamic law remains relevant, fair, and contextual in responding to the dynamics of community life. This article demonstrates that the flexibility of Islamic law does not conflict with divine principles, but precisely reflects the mercy and benevolence that are its goals.